Efficient, stable and selective adsorption of heavy metals by thio-functionalized layered double hydroxide in diverse types of water - Ali, Jawad; Wang, Huabin; Ifthikar, Jerosha; Khan, Aimal; Wang, Ting; Zhan, Kun; Shahzad, Ajmal; Chen, Zhulei; Chen, Zhuqi (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Mn-MoS4 offered record high distribution coefficient, fast kinetics and enormous capacities.•Mn-MoS4 tolerate severe chemical conditions during field applications.•The soft binding sites in Mn-MoS4 bind heavy metals by dominant M-S complexation.•LDH structure provides protective sites for intercalated thio groups against oxidation. The designing of efficient, selective and stable adsorbents for heavy metals removal remained a challenging task, as most adsorbents did not exhibit consistent performance in diverse types of water. Unlike traditional adsorbents based on surface oxygen groups, thio-functionalized layered double hydroxide (LDH) as Mn-MoS4 was designed by inserting MoS42− anions into lamellar layers in LDH, and was applied as a highly stable, efficient and selective adsorbent for heavy metals removal. The record high distribution coefficient (Kd∼107–108mL/g), fast kinetics and enormous saturated uptake capacities (594, 564 & 357mg/g) for Hg2+, Ag+ and Pb2+ placed Mn-MoS4 as the most efficient adsorbent for the removal of such metals so far. Further, Mn-MoS4 can completely tolerate the impact of huge concentration of background electrolytes (Ca2+, Mg2+, Na+, Cl−, NO3− & SO42−), and effectively control the concentrations of Hg2+, Ag+ and Pb2+ ions from tap water, lake water or industrial wastewater far below the limitation in drinking water. Similarly, Mn-MoS4 is a potential filter due to its consistent performance over a broad pH range (from 2.0 to 11.0), changing ionic strength (up to 100mM) or in the presence of organic matters. These remarkable features originate from the dominant chemical adsorption mechanism through inner-sphere coordination between thio groups as soft Lewis acid and Hg2+, Ag+ and Pb2+ as soft Lewis bases. More interestingly, LDH layers offer protective space for intercalated MoS42− anions against oxidation, and facilitate Mn-MoS4 with the advantage of easy storage and application over other adsorbents.